The Role of Iranians in Emergence of Arabic Prosody - احمد امیدوار (مطالعات زبانی و بلاغی)
Old Arab scientists believe that prosody is a pure Arabic knowledge initiated by Khalil Ibn Ahmad, or Arabs were familiar with the poetic rhythms before the era of his life. So, they have ignored somewhat the impact of external factors. These external factors include the role of Indians, Greeks and Iranians. In fact, Iranian people have also contributed to the emergence of this knowledge. In this study the issue has been examined independently and it has been concluded that many poems have been written by Iranians before the invention of Arabic prosody and they were familiar with the rules of poetic rhythms, and Khalil Ibn Ahmad either has been directly influenced by the Iranians due to the fact that there were many Farsi speakers in the places such as Basra and Khorasan where he lived in, and also because of his relationship with Iranian scientists such as Ibn Muqaffa, or he was influenced by them indirectly as it can be examined in the field of learning poem industry from Iranians, and writing poems like theirs. Also, the Arab poets have learned some of the Specific meters of Persian poetry and Khalil has studied these poems and meters, and he has introduced them in prosody science.